2014
DOI: 10.3310/hta18660
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled trial of Tumour necrosis factor inhibitors Against Combination Intensive Therapy with conventional disease-modifying antirheumatic drugs in established rheumatoid arthritis: the TACIT trial and associated systematic reviews

Abstract: BackgroundRheumatoid arthritis (RA) is initially treated with methotrexate and other disease-modifying antirheumatic drugs (DMARDs). Active RA patients who fail such treatments can receive tumour necrosis factor inhibitors (TNFis), which are effective but expensive.ObjectiveWe assessed whether or not combination DMARDs (cDMARDs) give equivalent clinical benefits at lower costs in RA patients eligible for TNFis.DesignAn open-label, 12-month, pragmatic, randomised, multicentre, two-arm trial [Tumour necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 259 publications
0
18
0
Order By: Relevance
“…Data from the tumour necrosis factor inhibitors against combination intensive therapy (TACIT) study 141 were provided as AiC.…”
Section: Network Meta-analysis Resultsmentioning
confidence: 99%
“…Data from the tumour necrosis factor inhibitors against combination intensive therapy (TACIT) study 141 were provided as AiC.…”
Section: Network Meta-analysis Resultsmentioning
confidence: 99%
“…The TACIT study compared the efficacy of combination conventional DMARD therapy with TNFi in patients who met the British Society for Rheumatology/National Institute for Clinical Excellence (BSR/NICE) eligibility criteria for the use of TNFi therapy, and found that using combination DMARD was non-inferior to TNFi therapy, and substantially more cost effective. 18 A significant proportion (~40%) of patients randomised to combination DMARD therapy eventually required TNFi therapy, and the implication of the ORBIT study is that further savings could be made if patients who fail to make an adequate response to combination nbDMARD therapy were then treated with rituximab rather than TNFi therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Within these comparisons, trials were further grouped according to whether they used early RA populations or established RA populations, as patients with early and established RA may respond to treatment differently. 17,18,22 We used definitions of early and established RA as defined in the trials, and, when no definition was provided, a cut-off point of 3 years was used, which is generally consistent across the literature (e.g. Scott et al 22 ), bearing in mind that no fixed consensus exists.…”
Section: Methods Of Analysis/synthesismentioning
confidence: 99%
“…17,18,22 We used definitions of early and established RA as defined in the trials, and, when no definition was provided, a cut-off point of 3 years was used, which is generally consistent across the literature (e.g. Scott et al 22 ), bearing in mind that no fixed consensus exists. Examining definitions and mean disease durations across trials, a 3-year cut-off point seems appropriate.…”
Section: Methods Of Analysis/synthesismentioning
confidence: 99%